In vitro antifungal activity of aqueous-ethanolic extract of Allium jesdianum against fluconazole-susceptible and -resistant human vaginal Candida glabrata isolates - Somayeh Shahrokh; Ghasem Vahedi; Ali-Reza Khosravi; Mohammadreza Mahzounieh; Azizollah Ebrahimi; Aghil Sharifzadeh; Asad Balal (Shahrekord University of Medical Sciences, 2017)
Introduction: About 50% of women are diagnosed with an episode of vulvovaginal candidiasis (VVC) during first 25 years of their lives. Candida glabrata is considered the second most prevalent non-C. albicans species associated with VVC. In this study, we examined the antifungal effect of a medicinal plant, Allium jesdianum, as a natural therapeutic agent against fluconazole-susceptible and -resistant human vaginal C. glabrata isolates, collected from 2 groups of volunteers; healthy women and women with VVC. Methods: An aqueous-ethanolic extract of A. jesdianum was prepared by maceration method. Vaginal specimens were collected from 28 women diagnosed with VVC and eight healthy subjects. The specimens were cultured using fungal-specific media in optimum conditions. The antifungal susceptibility of clinical isolates of C. glabrata to the plant extract and fluconazole was evaluated according to the standard protocols. Results: Candida glabrata was found to be the major cause of vaginal infection among 15.2% of women with VVC. We could identify the Candida spp. yeasts that colonized the vagina of 35% of healthy women while 19% of the isolated yeasts strains were detected as C. glabrata. Moreover, 7.1% of isolates obtained from VVC-patients were fluconazole resistant. The results showed the antifungal effect of A. jesdianum against all fluconazole resistant and susceptible C. glabrata vaginal isolates. The MIC90 of aqueous-ethanol (A-EtOH) extract of A. jesdianum against C. glabrata isolates from both VVC-patients and healthy women was 3 mg/mL. Conclusion: Our results showed the promising antifungal efficacy of aqueous-ethanolic extract of A. jesdianum. A. jesdianum extract might be used as an alternative choice to treat the VVC infections caused by fluconazole resistant Candida spp.